2021
DOI: 10.1590/s1678-3921.pab2021.v56.02498
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted emulsions with biopolymers for spray-drying of lemongrass essential oil

Abstract: The objective of this work was to evaluate the partial replacement of gum arabic by modified starches on the spray-drying microencapsulation of lemongrass (Cymbopogon flexuosus) essential oil. The ultrasound-assisted emulsions were prepared with 30% (w/w) of wall material, 7.5% (w/w) of oil load, and 1:1 (w/w) replacement ratio for all treatments. After 16 hours, the incompatibility observed between gum arabic and octenyl succinic anhydride (OSA) starch did not affect the obtained microparticles, since the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Emulsion of lemongrass oil of varying viscosities was obtained using different gum types which showed that less viscous emulsion propels better atomization leading to the formation of better microcapsules. For example, emulsions of maize maltodextrin 20DE (0.0607 μ Pa·s) showed the best atomization followed by maize maltodextrin 10 DE (0.0717 μ Pa·s), cassava maltodextrin 10 DE (0.0803 μ Pa·s), modified starch Capsul™ OSA starch (0.1253 μ Pa·s) and GA (0.1778 μ Pa·s) 60 . It was evident that the structure and size of the gum molecule also influenced the encapsulation efficiency.…”
Section: Steps In Spray Drying Processmentioning
confidence: 97%
See 1 more Smart Citation
“…Emulsion of lemongrass oil of varying viscosities was obtained using different gum types which showed that less viscous emulsion propels better atomization leading to the formation of better microcapsules. For example, emulsions of maize maltodextrin 20DE (0.0607 μ Pa·s) showed the best atomization followed by maize maltodextrin 10 DE (0.0717 μ Pa·s), cassava maltodextrin 10 DE (0.0803 μ Pa·s), modified starch Capsul™ OSA starch (0.1253 μ Pa·s) and GA (0.1778 μ Pa·s) 60 . It was evident that the structure and size of the gum molecule also influenced the encapsulation efficiency.…”
Section: Steps In Spray Drying Processmentioning
confidence: 97%
“…For example, emulsions of maize maltodextrin and GA (0.1778 μ Pa•s). 60 It was evident that the structure and size of the gum molecule also influenced the encapsulation efficiency.…”
Section: A | Process Of Emulsion/slurry Preparationmentioning
confidence: 99%
“…Due to its high cost, there are attempts to replace it with other materials. [17] Carvalho and collaborators [24,25] suggested the partial replacement of arabic gum by starch modified with octenyl succinic anhydride (OSA-starch) in a 1:1 ratio (w/w), which presented higher LEO retention (81.2%) than only arabic gum (67.5%), higher size distribution homogeneity, lower moisture content, and greater solubility. The oil retention was even better than the arabic gum/ maltodextrin combination (55%-67.5%), indicating the potential of using modified starch to obtain microcapsules by spray drying at a lower cost.…”
Section: Spray Dryingmentioning
confidence: 99%
“…It could be explained by EO's high volatility, which leads to a minor loss during the spray drying using lower temperatures. The spray dryer inlet temperatures used by other authors to encapsulate LEO were 165°C, [27,28] 170°C, [23][24][25] and 180°C. [22] The spray dryer temperature directly influences the microparticle morphology, as high heating causes faster drying of the wall material compared with the core, which can produce cracks and pores on the surfaces of the particles, leading to oil leakage.…”
Section: Spray Dryingmentioning
confidence: 99%